EVALUASI IMPLEMENTASI PROGRAM MANAJEMEN BERBASIS SEKOLAH PADA SMK NEGERI 3 JAKARTA - Dikson Silitonga (Lembaga Riset dan Pengabdian Masyarakat (LRPM) Institut Bisnis Nusantara, 2020)
In order to increase and equalize the educational quality in Indonesia, the government implements a new paradigm in running education with the orientation toward the need of each schools and regions, which is known as School Based Management Program.By using the Stake’s Countenance evaluation model, this research uses a qualitative and descriptive statistic (simple quantitative) approach with the techniques of data collection through a library study as secondary data sources, deep interviews and observation as primary data sources.Evaluation on the transaction phase (implementation program) shows that the implementation of School Based Management program at the SMK Negeri 3 Jakarta principally runs well in accordance with School Work Plan and Budget with is based on the regional government program, starting from planning, organizing, actuating, controlling, evaluation and monitoring, and budgeting. This means that the program has met the criteria of accuracy, suitability, adequacy and responsiveness. Toward these achievements, communities participation such us School Committee, parents, private sectors and industries are very large or significant.